Numerical simulation of mutual convective heat transfer and Soret-Dufour Effects in a MHD nanofluid-filled porous enclosure with fractal barriers - Zahir Shah; Muhammad Salim Khan; M. Sulaiman; Kholod M. Abualnaja; Muhammad Asif (Case Studies in Thermal Engineering)
This study presents a numerical investigation of mutual convective heat and mass transfer in a magnetohydrodynamic (MHD) nanofluid-filled porous enclosure featuring fractal internal barriers. The analysis includes the coupled effects of Soret and Dufour diffusion mechanisms. The enclosure is subjected to thermal conditions, with heat transport driven by buoyancy and cross-diffusion phenomena. The presence of fractal barriers introduces geometrical complexity that changes the flow topology and enhances thermal stratification and solute mixing. Key parameters such as the Hartmann number, Darcy number, Soret and Dufour numbers, and the fractal geometry configuration are systematically varied to explore their influence on flow structure, temperature distribution, concentration profiles, and entropy generation. Results indicate that the introduction of fractal barriers enhances the Nusselt number by a margin and the Sherwood number by up to 22%, compared to smooth-walled enclosures. Increased magnetic intensity reduces entropy generation by 15% due to flow damping. The cross-diffusion terms (Soret and Dufour) significantly influence stratification and entropy behavior, with peak irreversibility arising near barrier interfaces. This study demonstrates the thermal solutal performance improvement offered by fractal geometries in porous media under MHD conditions, relevant to solar collectors, energy storage systems, and biomedical devices.